The United Nations and the Imperatives for Implementing the Rules of International Development Law - Nemouchi, Nesrine (Journal of Ecohumanism, 2026)
This article examines the United Nations’ role in promoting and operationalizing international development law, with particular emphasis on the normative and institutional architecture through which development has been framed as a shared international objective and a human right. It analyses key instruments such as the 1986 Declaration on the Right to Development and the 2030 Agenda for Sustainable Development, alongside the contributions of UN organs including ECOSOC and UNDP in shaping policy guidance and disseminating development norms.The study finds that, despite significant normative consolidation, implementation remains structurally constrained by the predominantly soft-law character of international development law, donor-driven financing patterns, and asymmetric power relations within the UN system. It concludes that strengthening compliance requires more binding monitoring mechanisms and more inclusive participation of developing countries in agenda-setting and development governance.